Tumor Patients´ Perceived Changes of Specific Attitudes, Perceptions, and Behaviors Due to the COVID-19 Pandemic and Its Relation to Reduced Wellbeing - Büssing, Arndt; Hübner, Jutta; Walter, Stefanie; Gießler, Wolfgang; Büntzel, Jens (Frontiers in Psychiatry, 2020)
Background: During the COVID-19 pandemic, tumor patients reported fears and mental stress. We aimed to analyze whether tumor patients perceived changes in their attitudes and behaviors (related to relationships, awareness of nature and quietness, interest in spiritual issues, or feelings of worries and isolation) and how these perceived changes could be predicted, either by meaning in life, spirituality as a resource, perceived fears and worries, or particularly by their wellbeing. Materials and Methods: Online survey with standardized questionnaires among 292 tumor patients (72% men; mean age 66.7 ± 10.8 years) from Germany between May 6 to June 10, 2020. Results: Patients´ wellbeing (WHO5) scores were in the lower range (14.0 ± 6.1); 40% scored < 13, indicating depressive states. Wellbeing was significantly higher in older persons and low in younger ones (F=6.4, p=.002). Because of the restrictions, patients noticed changes in their attitudes and behaviors (measured with the 12-item Perceptions of Change Scale): 1) Perception of nature and silence, 2) Worrying reflections and loneliness, 3) Interest in spirituality, and 4) Intense relationships. These perceptions of change were similar in women and men, age groups and also with respect to tumor stages. Regression analyses revealed that Perception of nature and silence was predicted best by patients´ wondering awe and gratitude and by their search for meaning in life. Worrying reflections and loneliness was predicted best by their search for meaning and by feelings of being under pressure because of the Corona pandemic. Interest in spirituality was predicted best by search for an access to a spiritual source and by frequency of praying. Intense relationships were explained with weak predictive power by patients´ ability to reflect life concerns. Patients´ wellbeing during the COVID-19 pandemic was predicted by a mix of disease and pandemic related stressor, and by available resources (meaning in life and religious trust). Conclusion: The topics meaning in life, having (religious) trust, stable relationships, mindful encounter with nature, and times of reflection were of importance. To overcome tumor patients´ feelings of isolation, depressive states, and insecurity about future perspectives, further support is needed, particularly in their socio-spatial surrounding.